The millipede family Striariidae Bollman, 1893. IX. The identity of Striaria californica Cook, 1899, and the new genus Bayaria for Striaria nana Loomis, 1936, with a key to genera and an annotated checklist of the Striariidae (Diplopoda, Chordeumatida, Striarioidea) - Shear, William A.; Marek, Paul E. (Zootaxa, 2024)
The identity of Striaria californica Cook, described in 1899 from a single female, is established on the basis of additional specimens collected by Cook in 1929 and determined to be that species by Loomis (1936) as well as specimens from the San Francisco Bay region, likely to be from near the original collection locality. We propose Amplaria californica (Cook, 1899) new combination. A new genus, Bayaria Shear & Marek n. gen., is established for Striaria nana Loomis, 1936 Bayaria nana (Loomis, 1936) new combination. Striaria carmela Chamberlin, 1947, is a junior synonym of Bayaria nana. A key to the 16 genera of Striariidae and an annotated checklist of the 52 species are provided.